Evaluating the role of reputational risk on the performance of banks - Ullah, Naqeeb; Asghar, Umair (2023)
The purpose of the study was to evaluate the role of reputational risk on the performance of banks in Pakistan. For this research, the data was collected through the primary quantitative technique where the survey was conducted from the 100 bank managers of Pakistan. The data was analysed through correlation and regression analysis using SPSS software. The findings of the study state that reliability and integrity have a negative and insignificant influence over bank performance. While on the other hand, quality of financial product and services are found to have positive and significant influence on bank performance which suggests that an increase in the quality of financial product leads to an increase in Pakistani banks' performance. Further, Customer care has also been found to have positive and significant influence on bank performance. The study has certain limitations such as the sample size which is small and data generalizability can be an issue. Furthermore, the secondary data was not used as there is no such reputation index of Pakistan. Therefore, the future studies can consider various risk factors in evaluating their effect on bank performance. Further, future research can be considered developing reputation index for Banks using secondary quantitative data.